Novel genetic loci and a functional gene Gm18GRSC3 conferring SMV-SC3 resistance in soybean - Jiahao Chu; Wenlong Li; Zhenqi Shao; Zhanwu Yang; Xinzhu Xing; Hua Zhang; Rui Tian; Huantao Zhang; Xihuan Li; Caiying Zhang (Crop Journal)
Soybean mosaic virus (SMV) is a worldwide disease significantly decreasing soybean yield and seed quality. In this study, a genome-wide association study (GWAS) for SMV-SC3 resistance was conducted by using a deep re-sequencing dataset of 547 soybean accessions. A total of 11,405 SNPs and 1566 InDels were significantly associated with disease index (DI) at seedling stage and eight yield- and seed quality-related traits to SC3 resistance under eight environments. Among these genetic loci, 952 SNPs and 118 InDels were firstly identified to control SC3 resistance, and 52.42% and 42.37% of them were pleiotropic loci across multiple environments. Notably, the 8.47–8.89 Mb genomic region on chromosome 18 was firstly discovvered to associate with DI at seedling stage and four related traits at adult stage across multiple environments. Furthermore, the causal gene Gm18GRSC3 was identified and validated in this stable and pleiotropic locus for resistance to SC3 via positive and negative transgenic strategies. Overexpression of Gm18GRSC3 significantly decreased the accumulation of SC3 in transgenic soybean hairy roots, while silencing of Gm18GRSC3 significantly increased SC3 accumulation in soybean leaves. A functional marker, FM18GSC3, was developed based on the allelic variation of Gm18GRSC3, and the detection efficiency reached to 76% in another 100 soybean accessions. These findings provide valuable genetic loci and a functional gene for the improvement of SMV resistance in soybean.